Supra-threshold contrast perception in glaucomatous and normal human subjects - Utine, Canan Aslı. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2006., 2006)
The lateral inhibition mechanism of the sensorineural retina provides our visual systemwith a mean to sharpen the boundary between different luminances. Contrast is defined as the ratioof the difference in the luminance of two adjacent areas to the summation these luminance values. Contrast sensitivity is a measure of the ability of an individual to detect a difference in theluminance between two areas.Especially in the early stages of the chronic open angle glaucoma, contrast sensitivitychanges are seen earlier that visual field and optic nerve head changes. The usefulness and benefit of contrast-sensitivity testing include uncovering the hidden loss of vision not apparent throughother visual evaluations, providing a visual method to monitor the impact of treatmentintervention, and providing insights into the extent of patients̕ visual disability and functionalperformance problems. The simultaneous lightness contrast (SLC) effect demonstrates that the lightness of anobject depends on its immediate surround. A region seen against a dark background looks lighterthan an identical region seen against a light background.A modified SLC test was used to uncover the changes in the normal enhancement of contrast increments and decrements, due to deleterious effects of the glaucoma on neurosensorialretina. Both normal and glaucomatous subjects were found to overestimate contrast decrements ina similar manner. However, glaucomatous subjects failed to demonstrate enhancement of thecontrast increments, except for the largest increment. The test seem to detect the supra-threshold contrast sensitivity changes that occur before the visual field defects appear and classical thresholdcontrast sensitivity tests appear abnormal. It can be the first-line test in early stage and suspectedglaucoma cases. Additionally, other subjective visual assessment tests performed on glaucomatouspatients should be revised based on this concept.|Keywords: Contrast sensitivity function, glaucoma, simultaneous lightness contrast, suprathreshold contrast perception.
Keywords: Glaucoma.; Contrast sensitivity (Vision); Visual perception.; Brightness perception.